ROLE OF PHYTOESTROGENS IN PREVENTION OF OSTEOPOROSIS - Pankova, Stefka; Tsvetkova, Dobrina (International Journal of Current Pharmaceutical Research, 2015)
Osteoporosis is a disease characterized with the disbalance between the bone-building activity of osteoblasts and the re absorptive activity of osteoclasts. Estrogen deficiency occurring after menopause leads to enhanced risk of sudden fractures due to reduced bone mass. Phytoestrogens are polyphenolic plant metabolites: isoflavonoids, flavonoids (flavones, flavanones, chalcones), lignans, stilbenes. Phytoestrogens possess estrogenic activity and display the higherÂ affinityÂ for Î²-estrogen receptor due to their structural similarity to 17Î²-Estradiol. It is reported that bone loss is suppressed by Genistein and Daidzein from soy products, Quercetin and Rutin, Resveratrol from grapes and red wine, Kaempferol and Apigenin, Hesperidin, (+)-Catechin and Epigallocatechin gallate from green tea and Oleuropein. The most effective isoflavone in preserving bone health appears to be Genistein, which stimulates osteoblast and inhibits osteoclast function. Osteo protective effect of Formononetin on skeletal system results from the inhibition of osteoclastogenesis. Effects of Coumestrol on osteoblasts and osteoclasts are in increasing the bone density and preventing of bone resorption. Bioactive flavonoids enhance bone formation and inhibit bone resorption through their action on cell signaling pathways that influence osteoblast and osteoclast differentiation. 8-Prenylnaringenin promotes osteoblastic differentiation and inhibits bone resorption activity of osteoclasts by inducing ot their apoptosis. Plant lignans have been shown to provide estrogenic support, antioxidant and anti-inflammatory activity. Stilbene antioxidant Resveratrol exerts potential to attenuate bone loss due to multiple actions on both osteoblasts and osteoclasts. Monoterpene components from essential oils protects from bone loss. Due to inhibitory of the osteoclast activity.